2020
DOI: 10.1111/joim.13083
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of type 2 diabetes risk in black Africans: a South African perspective

Abstract: The prevalence of type 2 diabetes (T2D) is higher in black Africans than their European counterparts. This review summarizes the research exploring the pathogenesis of T2D in populations of African ancestry compared to white Europeans and shows that the pathogenesis differs by ethnicity. Black Africans present with a phenotype of low insulin sensitivity and hyperinsulinaemia as a result of increased insulin secretion and reduced hepatic insulin clearance. Whether hyperinsulinaemia precedes insulin resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…Our results in the IRAS Family Study and MILES suggest this may not be the case in African Americans, Hispanics, or non-Hispanic Whites. This is noteworthy given that numerous studies have found that insulin clearance is decreased in individuals of African descent, compared to other racial groups, and is a driver of hyperinsulinemia [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results in the IRAS Family Study and MILES suggest this may not be the case in African Americans, Hispanics, or non-Hispanic Whites. This is noteworthy given that numerous studies have found that insulin clearance is decreased in individuals of African descent, compared to other racial groups, and is a driver of hyperinsulinemia [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in AA, IMAT may play a larger role in insulin resistance. In addition to higher levels of IMAT, it has been hypothesized that the increased risk of insulin resistance observed in AA may also be a consequence of higher insulin secretion, decreased hepatic insulin clearance and increased mitochondrial efficiency/oxidative stress 37,38 . It is possible that in AA children and adults, these unique metabolic/endocrine phenotypes have a larger influence on the pathogenesis of insulin resistance compared to other racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most of the reported cross-sectional studies that have explored the associations between cortisol and cardiometabolic risk factors were conducted in non-Africans ( 3 , 4 , 5 , 6 ). Africans have a different metabolic phenotype to that of their European counterparts ( 11 , 12 ). Some studies have shown that in urban settings Africans have a higher prevalence of obesity and insulin resistance, yet have less visceral adipose tissue (VAT) than Europeans ( 13 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%